Sport science and innovation at the netherlands olympic committee - Maase, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Former elite distance runner Kamiel Maase is performance manager sport science & innovation at the Netherlands Olympic Committee (NOC*NSF). In this role, he contributes to bridging the well-known gap between science and sports on a daily basis. A solid foundation has been built over the past seven years. His work involves, of course, interaction with both coaches and academics. But he interacts with businesses as well. His network has expanded and numerous projects - some highly academic, others very practical - have been carried out. With the 2016 Rio Olympics approaching, coaches and athletes demand evidence-based, practical advice as well as concrete innovations supporting performance. Kamiel explains how NOC*NSF approaches applied sport science and innovation, and will present specific examples of projects, both long-term and short-term, on the Road to Rio. The presentation is part of the ACSM-ECSS exchange symposium. Randy Wilber (US Olympic Committee) will represent the United States. The presentations will allow comparisons between the US and European approach to be made.